IMPLEMENTASI PROFIL PELAJAR PANCASILA DALAM EKSTRAKURIKULER TARI BERBASIS KEARIFAN LOKAL DI SD NEGERI GIRIKERTO 2 - Vivin Setyani; Novia Rahma Rista Utami; Desi Nuzul Agnafia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Pancasila Student Profile is used as a guideline in the process of shapingstudent character in accordance with the noble values of the Indonesian nation. Atthe elementary school level, which is the first stage of formal education, its role iscrucial in shaping character values and national culture for all students. Thepurpose of this research is to: (1) Determine the planning of art extracurricularactivities at SD Negeri Girikerto 2. (2) Determine the implementation of danceextracurricular activities at SD Negeri Girikerto 2. (3) Determine the evaluation ofdance extracurricular activities at SD Negeri Girikerto 2. This research uses aqualitative approach with a descriptive method. Data collection techniques includeobservation, interviews, and documentation. The results show that theimplementation of the Pancasila Student Profile in dance extracurricular activitiesbased on local wisdom at SD Negeri Girikerto 2 is carried out through planning,implementation, and evaluation processes. This activity has implemented sixdimensions of the Pancasila Student Profile and promotes positive developmentfor students' talents and the school. Through the Orek-Orek dance, a traditionaldance from Ngawi, this extracurricular activity also builds cultural identity andinstills the noble values of traditional arts in students.